Penentuan Daya Dukung Perairan untuk Perikanan Alami (Studi Kasus: Situ Cilala, Kabupaten Bogor) - Novita MZ; Kadarwan Soewardi; Niken Tunjung Murti Pratiwi (Institut Pertanian Bogor, 2015)
This study aimed to assess the aquatic carrying capacity for extensive fishing. The study was conducted in Cilala Lake, Jampang Village, Bogor. The carrying capacity was determined based on primary productivity using the chlorophyll value, which is indicating the existence of phosphate in waters. The result showed that carrying capacity of Cilala Lake for extensive fishing was 3.51 tons/year. Tilapia was the fish which could be restocked, because it has high tolerance to waters condition and there’s not prey or predator for this fish. If fish for restocking was assumed about 25 g in size and would be about 250 g after 46 months (harvest size), then the maximum stocked was 15.602 fingerlings/year for two periods. The number of fish pen cage available on the lake should be considered in calculating the number of fish for restocking.